Heat Shock Protein as Molecular Targets for Breast Cancer Therapeutics - Kim, Lee Su (Korean Breast Cancer Society, 2011)
Recent advances in the understanding of the molecular mechanisms involved in the breast cancer development and progression have led to the identification of numerous novel molecular targets. Among these, heat shock proteins (HSPs) are being emerging molecular target due to its diverse function in cancer cells. HSPs are highly conserved molecular chaperone that are synthesized by cell in response to various stress conditions. Mammalian HSPs have been classified into several families according to their molecular weight: HSP100, HSP90, HSP72, and small molecular HSPs (including HSP27). They are essential proteins that play a key role in cell survival through the cytoprotective mechanisms. In addition, HSPs are often overexpressed in a rage of cancers including breast cancer, and its overexpression seems to be associated with poor clinical outcomes. Also, HSP90 play a role in facilitating transformation by stabilizing the mutated and overexpressed oncoproteins found in breast cancer cell. Pharmacological targeting of HSP is therefore indicated and in the case of HSP90, numerous inhibitory drugs are undergoing clinical trial for treatment of breast cancer and other cancers. In this review, we describe the roles of HSPs in cancer cell and introduce the HSPs inhibitor as molecular target in cancer therapy and its recent clinical trials in breast cancer.